MEDIA PEMBELAJARAN GOOGLE CLASSROOM DAN MOTIVASI BELAJAR FISIKA PESERTA DIDIK DI MASA PANDEMI COVID-19 - Handayani, Yusri; Nurfadilah (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This research is a quantitative study with a correlative method that was carried out at SMP Unismuh Makassar with the aim of knowing the effect of the Google Classroom learning media on students' motivation to learn physics during the COVID-19 pandemic. The population in this study were students of class VII, VIII, IX SMP Unismuh Makassar in the academic year 2021-2022. The sample in this study used random sampling technique so that the research sample obtained was 77 people. Collecting research data using a learning motivation questionnaire/questionnaire with scoring guidelines using a Likert scale. Hypothesis testing was carried out by correlation test analysis and simple linear regression with SPSS 24 which showed that there was an influence of the google classroom learning media on the students' motivation to learn science during the COVID-19 pandemic.